2020
DOI: 10.5539/hes.v10n1p121
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Perceptions of the Effectiveness of Online Professional Development in Higher Education in Saudi Arabia

Abstract: This study aimed at examining EFL teachers’ perceptions of the effectiveness of an OPD program provided by a Saudi University. The program lasted for almost one year, and consisted of different courses about teaching English language. An online questionnaire was sent to the teachers to examine their perceptions of the effectiveness of the program through examining teachers’ perceptions of the significant features of the program, their learning in the program, and their use of the new knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
4
9
1
Order By: Relevance
“…This participation was in the form of using different tools of online professional development such as web-based activities, social networks, and online communities of practice. These findings are supported by previous studies in which teachers reported participating in online professional development using social networks, webinars, and online communities for professional development (Alzahrani & Althaqafi, 2020;Poole et al, 2020). However, the rate of teachers' participation in online professional development activities in this study (58.25%) is not significantly higher than those who did not participate (41.15%).…”
Section: Discussion Of the Findings 51teachers' Participation In Online Professional Development Activitiessupporting
confidence: 86%
See 2 more Smart Citations
“…This participation was in the form of using different tools of online professional development such as web-based activities, social networks, and online communities of practice. These findings are supported by previous studies in which teachers reported participating in online professional development using social networks, webinars, and online communities for professional development (Alzahrani & Althaqafi, 2020;Poole et al, 2020). However, the rate of teachers' participation in online professional development activities in this study (58.25%) is not significantly higher than those who did not participate (41.15%).…”
Section: Discussion Of the Findings 51teachers' Participation In Online Professional Development Activitiessupporting
confidence: 86%
“…This effectiveness is confirmed by the results of many studies in different contexts (Alzahrani & Althaqafi, 2020;Hussein, 2013;Poole et al, 2020). In the present study teachers also perceived that online professional development activities are not effective in fostering active and collaborative participation in professional development which contradicts the results of other studies in which teachers' reported the efficacy of online professional development in promoting active and collaborative participation in professional development (Alzahrani & Althaqafi, 2020;Poole et al, 2020). These contradictory results in the Moroccan context could be attributed to teachers' preference of traditional forms of professional development that keeps the face-to-face contact and interaction, and also to the fact that teachers' in this study participated only in informal forms of online professional development that don't meet all the characteristics of effective professional development.…”
Section: 3teachers' Perceived Effectiveness Of Online Professional Development Activitiessupporting
confidence: 71%
See 1 more Smart Citation
“…A second study (Abed & Shackleford, 2020) was excluded as it focused on learning disabled students and how to support them. A third study (Alzahrani & Althaqafi, 2020) was excluded as it focused on teachers' perceptions of online professional development. A fourth study (Alyami, 2020) was excluded as it focused on e-learning integration from the perception of concerned bodies: administrators and policy makers.…”
Section: Rationale For Choosing the Criteriamentioning
confidence: 99%
“…Well-designed OTPDPs are supposed to encourage attendees to interact, share knowledge and experience, and improve themselves professionally (Eun, 2008;SREB, 2004). Alzahrani and Althaqafi (2020) also stated that OTPDPs helped teachers acquire professional knowledge and develop professional skills. Our results are consistent with the literature (Dede, 2006;INACOL, 2011;ISTE, 2008;Scott & Scott, 2010).…”
Section: Discussionmentioning
confidence: 99%